La prise en charge de la biodiversité entre absence, instrumentalisation économique et biopolitique des comportements : les plans de paysage au prisme du néolibéralisme - Alissia Gouju (Développement Durable et Territoires)
Based on the study of the institutional documents of the landscape plans and on an empirical investigation carried out on one of its local applications, the text proposes to think about the place occupied by the biodiversity, and its potential losses, in this plan. Conceived as a potential lever for territorial development, the preservation of biodiversity is not a priority but also almost absent from landscape plans. As an integral part of the landscape, it is used for the purposes of commodification and territorial competition in a neoliberal application of public policies. Standardized and instrumentalized, biodiversity becomes a justification and a way of governing people.